2009
DOI: 10.1371/journal.pntd.0000447
|View full text |Cite
|
Sign up to set email alerts
|

Strong Host-Feeding Preferences of the Vector Triatoma infestans Modified by Vector Density: Implications for the Epidemiology of Chagas Disease

Abstract: BackgroundUnderstanding the factors that affect the host-feeding preferences of triatomine bugs is crucial for estimating transmission risks and predicting the effects of control tactics targeting domestic animals. We tested whether Triatoma infestans bugs prefer to feed on dogs vs. chickens and on dogs vs. cats and whether vector density modified host choices and other vital rates under natural conditions.MethodologyTwo host choice experiments were conducted in small caged huts with two rooms between which bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 55 publications
1
94
1
1
Order By: Relevance
“…Notably, we observed that, when mouse, dog, and chicken blood was identified in T. dimidiata, human blood was also identified, suggesting that the vector is able to disperse between peridomicile and domicile sites to search for better host availability and accessibility as previously reported. 21 The above data, in addition to the infection index of triatomines trapped inside houses of 38%, may suggest that high risk of T. cruzi infection to humans could exist in this community, but seroprevalence against T. cruzi in the population revealed only 2.3% (3/128). This seroprevalence is low compared with other endemic regions, such as the states of Chiapas and Oaxaca in Mexico (their seroprevalence is above 10%), 22 and exceptionally high 67% and 32% in some communities of Oaxaca and Chiapas, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Notably, we observed that, when mouse, dog, and chicken blood was identified in T. dimidiata, human blood was also identified, suggesting that the vector is able to disperse between peridomicile and domicile sites to search for better host availability and accessibility as previously reported. 21 The above data, in addition to the infection index of triatomines trapped inside houses of 38%, may suggest that high risk of T. cruzi infection to humans could exist in this community, but seroprevalence against T. cruzi in the population revealed only 2.3% (3/128). This seroprevalence is low compared with other endemic regions, such as the states of Chiapas and Oaxaca in Mexico (their seroprevalence is above 10%), 22 and exceptionally high 67% and 32% in some communities of Oaxaca and Chiapas, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Culex nigripalpus, a major vector for Saint Louis encephalitis in the southern United States, preferred chickens to bobwhite quail in a host-choice experiment in Florida, USA [64]. Host preferences are not exclusive to mosquitoes: Triatoma bugs that transmit Chagas' disease demonstrated strong feeding preferences for dogs over both chickens and cats in a recent study [65]. At least one species of tsetse fly (Glossina morsitans morsitans), vector of human (sleeping sickness) and animal trypanosomiasis in Africa, show feeding preferences towards buffalo and oxen but avoid other hosts such as waterbuck (reviewed in [66]).…”
Section: Discussionmentioning
confidence: 99%
“…Various factors such as season, developmental stage, and vector density, may affect the feeding patterns of vectors, thus it would be important to monitor blood sources at different times of the year if blood sources are to be used to evaluate control programs. 32,33,35,36 Although there was a significant decrease in vectors containing dog blood meals, dogs remain an important reservoir animal in Guatemala, as they are elsewhere [37][38][39] ; the majority of the blood meals found before the interventions were dog, and even after the interventions nearly 30% of vectors had fed on dog. Usually houses have many dogs and there is no breeding control.…”
Section: Discussionmentioning
confidence: 99%